Development of Digital Skills and Engineering Thinking in Students as Part of the Digital Summer Project - Anisimova, Tatyana; Ganeeva, Aigul; Sharafeeva, Landysh (International Journal of Engineering Pedagogy (iJEP), 2021)
Digitalization of the economy is a key priority for Russia today, which makes the problem stated herein relevant. Personal motivations, values, mor-als, and ethics are of increasing importance. In this regard, project, flexible, and soft skills are coming to the fore; these include digital skills such as the ability to confidently, effectively, critically, and safely pick and apply in-formation and communication technologies in various aspects of life. Re-search and experimentation skills, being an integral part of engineering cul-ture and thinking, stay relevant, too. The purpose of the study is to prove the effectiveness of developing digi-tal competencies and engineering thinking in children and young people dur-ing the Digital Summer project, developed as part of a grant for conducting thematic sessions in advanced areas of discrete mathematics, informatics, and digital technologies. In the course of the study, effectiveness was assessed by mathematical processing of the results of questionnaires and surveys of session partici-pants. The results of the study allow concluding that it is possible to translate the experience gained into the system of working with children and youth.